An environmentally friendly water-based cutting fluid with excellent lubrication and rust prevention properties and a preparation method thereof
By using citric acid-carbon dot composite in water-based cutting fluid, the problem of long run-in period and difficulty in taking into account both lubrication and rust prevention in the existing water-based cutting fluid is solved, and the ultra-lubricating state is achieved in the short run-in period and the possession of the existing water-based cutting fluid is achieved. Good anti-rust performance effect.
Patent Information
- Application Number
- CN202310354323.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-06
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-04-06
AI Technical Summary
When the existing water-based cutting fluid achieves superlubrication on the friction pair surface, the running-in period is long, resulting in severe wear and tear in the friction pair, and it is difficult to take into account the anti-rust performance.
Using a combination of water, polyethylene glycol and citric acid-carbon dot complex, the citric acid-carbon dot complex is prepared by citric acid through pyrolysis reaction, and is dispersed in water by ultrasonic to form an excellent lubricating and anti-rust properties. Water-based cutting fluid.
It achieves ultra-lubricating state (friction coefficient less than 0.01) within a short run-in period (30~150s), and has good anti-rust performance, reducing friction and wear, while reducing raw material costs and usage costs, and is environmentally friendly.
Smart Images

Figure CN116376629B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of cutting fluid, and in particular to an environmentally friendly water-based cutting fluid with excellent lubrication and rust prevention properties and a preparation method thereof. Background Art
[0002] Cutting fluid is a liquid commonly used in the metal cutting industry. It can greatly reduce the friction and heat generated by friction during the cutting process, reduce the wear of the cutting tool, and improve the precision and quality of the processing. Therefore, this requires the cutting fluid to have excellent lubrication, rust prevention, cooling, and cleaning properties. At present, cutting fluids can be divided into oil-based cutting fluids and water-based cutting fluids according to the components. Among them, oil-based cutting fluids often have poor cooling performance, high cost of use, and will also pollute the environment, etc., which limits their application in the field of industrial cutting. Although the existing water-based cutting fluids have good cooling and cleaning properties, their lubrication properties are poor. Although the water-based cutting fluids with superlubricity or ultra-low friction coefficients disclosed in Chinese patents CN113403131A and CN113046163A can achieve a superlubricity state (friction coefficient less than 0.01), the required running-in period is relatively long (200 to 1500s). When the friction coefficient is reduced to 0.01 to achieve a superlubricity state, the friction pair may have suffered serious wear.
[0003] In addition, due to the presence of water in the cutting fluid, the tool and workpiece surface are prone to rust. At present, commercial cutting fluids on the market often cannot take into account both rust prevention and lubrication functions at the same time. Therefore, it is of great significance to develop and design a cutting fluid with extremely low friction coefficient and anti-corrosion and anti-rust functions. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an environmentally friendly water-based cutting fluid with excellent lubrication and rust prevention performance and a preparation method thereof. The water-based cutting fluid of the present invention has super lubrication (friction coefficient less than 0.01) performance and a short running-in period (30 to 150 seconds).
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides an environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties, comprising water, polyethylene glycol and a citric acid-carbon dot complex, wherein the mass ratio of the water, polyethylene glycol and the citric acid-carbon dot complex is 40-60:40-60:0.1-2, and the citric acid-carbon dot complex comprises citric acid and carbon dots.
[0007] Preferably, the mass ratio of water, polyethylene glycol and citric acid-carbon dot composite is 10:10:0.2, 10:15:0.1 or 30:20:0.5.
[0008] Preferably, the particle size of the carbon dots is 2 to 8 nm.
[0009] Preferably, the citric acid-carbon dot composite is prepared by thermal decomposition of citric acid.
[0010] Preferably, the temperature of the pyrolysis reaction is 150-250° C., and the time is 20-60 min.
[0011] Preferably, the temperature of the pyrolysis reaction is 200° C. and the time is 30 min.
[0012] Preferably, after the pyrolysis reaction, the pyrolysis product is dispersed in water to obtain a dispersion, and the dispersion is extracted with ethyl acetate and water in sequence, followed by rotary evaporation to obtain the citric acid-carbon dot complex.
[0013] Preferably, the polyethylene glycol includes one or more of polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000, polyethylene glycol 10000 and polyethylene glycol 20000.
[0014] Preferably, the polyethylene glycol is a mixture of polyethylene glycol 4000 and polyethylene glycol 6000, and the mass ratio of polyethylene glycol 4000 to polyethylene glycol 6000 in the mixture is 2 to 5:1; or, the polyethylene glycol is a mixture of polyethylene glycol 8000 and polyethylene glycol 10000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 10000 in the mixture is 2 to 5:1; or, the polyethylene glycol is a mixture of polyethylene glycol 8000 and polyethylene glycol 20000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 20000 in the mixture is 2 to 5:1.
[0015] The present invention also provides a method for preparing the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties described in the above technical solution, comprising the following steps:
[0016] Polyethylene glycol, water and citric acid-carbon dot complex are mixed in sequence to obtain the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties.
[0017] The present invention provides an environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties, comprising water, polyethylene glycol and a citric acid-carbon dot complex, wherein the mass ratio of the water, polyethylene glycol and the citric acid-carbon dot complex is 40-60:40-60:0.1-2, and the citric acid-carbon dot complex comprises citric acid and carbon dots.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The water-based cutting fluid provided by the present invention can achieve superlubricity (extremely low friction coefficient) on the surface of metal friction pairs such as bearing steel, and its running-in period is relatively short. The reason is that: the carbon dots can be firmly adsorbed on the surface of the friction pair to form a solid lubrication film, and the graphene-like structure layers inside the carbon dots can easily slip to reduce friction; in addition, citric acid can complex with the surface of the steel block to reduce the direct contact between the rough peaks of the two friction pairs, thereby reducing friction and wear. The data of the embodiment show that the water-based cutting fluid provided by the present invention has excellent tribological properties after tribological testing, and can achieve superlubricity after a relatively short running-in period (1 to 3 minutes), with a friction coefficient of less than 0.01;
[0020] When the citric acid in the present invention undergoes a complex reaction with the metal friction pair, it can be adsorbed onto the surface of the friction pair, thereby making the water-based cutting fluid have better anti-corrosion and anti-rust properties;
[0021] The carbon dots (carbon quantum dot nanomaterials) in the present invention can reduce the direct contact of the rough peaks of the friction pair, reduce the wear of the metal surface, and can also be used as a surface polishing agent to ensure the accuracy and quality of metal processing;
[0022] The raw material cost of the invention is low, the use cost is low, it is easy to mass produce, and it will not cause pollution to the environment. It is safe for users and not easy to cause allergies. It can prepare high, medium and low-grade cutting lubricants according to needs to meet different needs.
[0023] Furthermore, the preparation method of the citric acid-carbon dot composite in the present invention is simple, does not need to convert all the citric acid into carbon quantum dots, and has a high yield. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A transmission electron micrograph of carbon quantum dots in the citric acid-carbon dot composite provided in Example 1;
[0025] Figure 2 The variation curve of the friction coefficient of the water-based cutting fluid provided in Example 1;
[0026] Figure 3 An optical photograph of the wear area on the steel block surface corresponding to the water-based cutting fluid provided in Example 1;
[0027] Figure 4 The distribution diagram of C, O and Fe on the steel block surface corresponding to the water-based cutting fluid provided in Example 1;
[0028] Figure 5 This is an EDS scan of the steel block surface corresponding to the water-based cutting fluid provided in Example 1;
[0029] Figure 6The variation curve of the friction coefficient of the water-based cutting fluid provided in Example 2;
[0030] Figure 7 This is a curve showing the change in the friction coefficient of the water-based cutting fluid provided in Example 3;
[0031] Figure 8 This is an optical photograph of the wear area on the surface of the steel block corresponding to the deionized water used in Comparative Example 1;
[0032] Fig. 9 The distribution diagram of C, O and Fe on the steel block surface corresponding to the deionized water used in Comparative Example 1;
[0033] Fig.10 This is the EDS scan of the steel block surface corresponding to the deionized water used in Comparative Example 1. DETAILED DESCRIPTION
[0034] The present invention provides an environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties, comprising water, polyethylene glycol and a citric acid-carbon dot complex, wherein the mass ratio of the water, polyethylene glycol and the citric acid-carbon dot complex is 40-60:40-60:0.1-2, and the citric acid-carbon dot complex comprises citric acid and carbon dots.
[0035] In the present invention, unless otherwise specified, the raw materials used are all commercially available products in the art.
[0036] In the present invention, the mass ratio of water, polyethylene glycol and citric acid-carbon dot composite is preferably 10:10:0.2, 10:15:0.1 or 30:20:0.5.
[0037] In the present invention, the water is preferably deionized water.
[0038] In the present invention, the particle size of the carbon dots is preferably 2 to 8 nm. The carbon dots as micro bearings can transform sliding into rolling, effectively reducing friction. The citric acid can complex with the surface of the steel block to reduce the direct contact between the rough peaks of the two friction pairs, thereby reducing friction and wear.
[0039] In the present invention, the citric acid-carbon dot composite is preferably prepared by thermal decomposition of citric acid.
[0040] In the present invention, the temperature of the pyrolysis reaction is preferably 150-250° C., more preferably 200° C., and the time is preferably 20-60 min, more preferably 30 min.
[0041] In the present invention, after the pyrolysis reaction, the pyrolysis product is preferably dispersed in water to obtain a dispersion, and the dispersion is extracted with ethyl acetate and water in sequence, and then subjected to rotary evaporation to obtain the citric acid-carbon dot complex.
[0042] In a specific embodiment of the present invention, the citric acid-carbon dot composite is prepared by the following steps:
[0043] First, anhydrous citric acid is placed in a beaker and heated at a temperature of 150-250° C. for 20-60 minutes. After the color of the citric acid changes from white to orange-yellow, deionized water is added to the beaker and ultrasonically dispersed for 10-30 minutes. The resulting dispersion is then extracted with ethyl acetate and deionized water, respectively, and subjected to rotary evaporation to obtain the citric acid-carbon dot complex.
[0044] In the present invention, since it is not necessary to pyrolyze all the citric acid into carbon dots, the yield of the method is 10-20%.
[0045] In the present invention, the polyethylene glycol preferably includes one or more of polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000, polyethylene glycol 10000 and polyethylene glycol 20000.
[0046] In the present invention, the polyethylene glycol is preferably a mixture of polyethylene glycol 4000 and polyethylene glycol 6000, and the mass ratio of polyethylene glycol 4000 to polyethylene glycol 6000 in the mixture is preferably 2-5:1; or, the polyethylene glycol is preferably a mixture of polyethylene glycol 8000 and polyethylene glycol 10000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 10000 in the mixture is preferably 2-5:1; or, the polyethylene glycol is preferably a mixture of polyethylene glycol 8000 and polyethylene glycol 20000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 20000 in the mixture is preferably 2-5:1.
[0047] The present invention also provides a method for preparing the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties described in the above technical solution, comprising the following steps:
[0048] Polyethylene glycol, water and citric acid-carbon dot complex are mixed in sequence to obtain the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties.
[0049] In a specific embodiment of the present invention, the preparation method comprises the following steps:
[0050] Firstly, polyethylene glycol is dissolved in water and ultrasonically treated for 20 to 30 minutes to obtain a polyethylene glycol aqueous solution; then, a citric acid-carbon dot complex is added thereto and ultrasonically treated for 20 to 30 minutes to make it dispersed evenly to obtain the water-based cutting fluid.
[0051] The present invention also provides an application of the water-based cutting fluid described in the above technical solution. The present invention has no special limitation on the specific manner of the application, and a manner familiar to those skilled in the art may be used.
[0052] In order to further illustrate the present invention, the water-based cutting fluid and the preparation method thereof provided by the present invention are described in detail below in conjunction with examples, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] First, anhydrous citric acid was placed in a beaker and heated at 200°C for 30 minutes. After the color of the citric acid changed from white to orange-yellow, deionized water was added to the beaker and ultrasonically dispersed for 30 minutes. The aqueous solution was then extracted and rotary evaporated with ethyl acetate and deionized water to obtain a citric acid-carbon dot complex. The transmission electron microscopy of the carbon quantum dots is shown in FIG. Figure 1 shown.
[0055] 10 g of polyethylene glycol 10000 was dissolved in 10 g of deionized water and subjected to ultrasonic treatment for 20 min to obtain a polyethylene glycol 10000 aqueous solution; then 0.2 g of the citric acid-carbon dot complex obtained in Example 1 was added thereto and subjected to ultrasonic treatment for 30 min to uniformly disperse the complex, thereby obtaining a water-based cutting fluid.
[0056] The tribological properties of the water-based cutting fluid were tested using a ball-on-disc friction and wear tester (TRB-3, Anton Paar). The upper friction pair used in the test was a GCr15 bearing steel ball with a diameter of 6 mm, and the lower friction pair was a bearing steel block with a diameter of 2.5 cm. The load used was 2N, the sliding distance was 2mm, the sliding frequency was 4Hz, and the test time was 30min. The wear scar area on the upper and lower bearing steel friction pairs was also observed using an optical microscope. The change curve of the friction coefficient of the water-based cutting fluid prepared in this embodiment is shown in Figure 1. Figure 2 As shown. Figure 2 It can be seen that after a 100-second running-in period, the friction coefficient of the water-based cutting fluid dropped to below 0.01, reaching a super-lubricating state; after 300 seconds, its friction coefficient stabilized between 0.006 and 0.007. Figure 3 As shown in the figure, after the friction test, the width of the wear scar on the steel block surface is about 106μm, and the surface of the wear scar area is flat and smooth without obvious grooves, indicating that it is suitable as a metal cutting fluid. Figure 4 and Figure 5 It can be seen that there is no obvious distribution of O element in the wear area on the steel block surface, indicating that the water-based cutting fluid has good anti-corrosion and anti-rust properties.
[0057] Example 2
[0058] First, anhydrous citric acid was placed in a beaker and heated at 150°C for 40 minutes. After the color of the citric acid changed from white to orange-yellow, deionized water was added to the beaker and ultrasonically dispersed for 20 minutes. The aqueous solution was then extracted and rotary evaporated with ethyl acetate and deionized water, respectively, to obtain a citric acid-carbon dot complex.
[0059] 15 g of polyethylene glycol 8000 was dissolved in 10 g of deionized water and ultrasonically treated for 30 minutes to obtain a polyethylene glycol 8000 aqueous solution; then 0.1 g of the citric acid-carbon dot complex obtained in Example 2 was added thereto and ultrasonically treated for 20 minutes to uniformly disperse it to obtain the desired water-based cutting fluid.
[0060] The tribological properties of the water-based cutting fluid were tested using a ball-on-disc friction and wear tester (TRB-3, Anton Paar). The upper friction pair used in the test was a GCr15 bearing steel ball with a diameter of 6 mm, and the lower friction pair was a bearing steel block with a diameter of 2.5 cm. The load used was 2N, the sliding distance was 2mm, the sliding frequency was 4Hz, and the test time was 30min. The wear scar area on the upper and lower bearing steel friction pairs was also observed using an optical microscope. The change curve of the friction coefficient of the water-based cutting fluid prepared in this embodiment is shown in Figure 2. Figure 6 As shown. Figure 6 It can be seen that after a 140s running-in period, the friction coefficient of the water-based cutting fluid dropped to below 0.01, reaching a super-lubricating state; after 900s, its friction coefficient stabilized between 0.005 and 0.007. After the friction test, the width of the wear scar on the steel block surface was about 124μm, and the surface of the wear scar area was flat and smooth without obvious grooves, indicating that it is suitable as a metal cutting fluid.
[0061] Example 3
[0062] First, anhydrous citric acid was placed in a beaker and heated at 250°C for 20 minutes. After the color of the citric acid changed from white to orange-yellow, deionized water was added to the beaker and ultrasonically dispersed for 20 minutes. The aqueous solution was then extracted and rotary evaporated with ethyl acetate and deionized water, respectively, to obtain a citric acid-carbon dot complex.
[0063] 30 g of polyethylene glycol 6000 was dissolved in 20 g of deionized water and ultrasonically treated for 30 minutes to obtain a polyethylene glycol 6000 aqueous solution; then 0.5 g of the citric acid-carbon dot complex obtained in Example 3 was added thereto and ultrasonically treated for 20 minutes to make it evenly dispersed to obtain the desired water-based cutting fluid.
[0064] The tribological properties of the water-based cutting fluid were tested using a ball-on-disc friction and wear tester (TRB-3, Anton Paar). The upper friction pair used in the test was a GCr15 bearing steel ball with a diameter of 6 mm, and the lower friction pair was a bearing steel block with a diameter of 2.5 cm. The load used was 3N, the sliding distance was 2 mm, the sliding frequency was 5 Hz, and the test time was 30 min. The wear scar area on the upper and lower bearing steel friction pairs was also observed using an optical microscope. The change curve of the friction coefficient of the water-based cutting fluid prepared in this embodiment is shown in Figure 2. Figure 7 As shown in the figure, after a 30-second running-in period, the friction coefficient of the water-based cutting fluid dropped to below 0.01, reaching a super-lubricating state; after 300 seconds, its friction coefficient stabilized between 0.005 and 0.007. After the friction test, the width of the wear scar on the surface of the steel block was about 110 μm, and the surface of the wear scar area was flat and smooth without obvious grooves, indicating that it is suitable as a metal cutting fluid.
[0065] Comparative Example 1
[0066] The friction performance test was carried out using deionized water as a water-based lubricating cutting fluid. The load used was 2N, the sliding distance was 2mm, the sliding frequency was 4Hz, and the test time was 30min. The friction coefficient of deionized water was as high as 0.3. The width of the wear scar on the surface of the steel block was about 340μm. The wear scar area was relatively rough, and obvious grooves could be observed. The corrosion in the wear scar area was also relatively serious ( Figure 8 ). Fig. 9 The distribution diagram of C, O and Fe on the steel block surface corresponding to the deionized water used in Comparative Example 1 is shown in FIG. Fig.10 This is the EDS scanning image of the steel block surface corresponding to the deionized water used in Comparative Example 1. Fig. 9 and Fig.10 It can be seen that there are more O elements in the wear area of the steel block surface corresponding to pure water, which also shows that its surface has undergone severe corrosion.
[0067] Comparative Example 2
[0068] The friction performance test was carried out using pure polyethylene glycol 10000 aqueous solution (where the mass ratio of polyethylene glycol to deionized water was 1:1) as a water-based lubricating cutting fluid, with a load of 2N, a sliding distance of 2mm, a sliding frequency of 4Hz, and a test time of 30min. The friction coefficient of the polyethylene glycol 10000 aqueous solution was about 0.02, the width of the wear scar on the steel block surface was about 206μm, and there were several obvious grooves in the wear scar area.
[0069] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. An environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties, characterized in that: The invention is composed of water, polyethylene glycol and a citric acid-carbon dot complex, wherein the mass ratio of the water, polyethylene glycol and the citric acid-carbon dot complex is 40-60:40-60:0.1-2, and the citric acid-carbon dot complex comprises citric acid and carbon dots; the citric acid-carbon dot complex is prepared by thermal decomposition of citric acid, wherein the temperature of the thermal decomposition reaction is 150-250°C and the time is 20-60 minutes.
2. The environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to claim 1, characterized in that: The mass ratio of water, polyethylene glycol and citric acid-carbon dot composite is 10: 10:0.2、10: 15:0.1 or 30:20:0.
5.
3. The environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to claim 1, characterized in that: The particle size of the carbon dots is 2 to 8 nm.
4. The environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to claim 1, characterized in that: The temperature of the pyrolysis reaction is 200° C. and the time is 30 minutes.
5. The environmentally friendly water-based cutting fluid with excellent lubrication and rust prevention properties according to claim 1, characterized in that: After the pyrolysis reaction, the pyrolysis product is dispersed in water to obtain a dispersion, and the dispersion is extracted with ethyl acetate and water in sequence, and then subjected to rotary evaporation to obtain the citric acid-carbon dot complex.
6. The environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to claim 1, characterized in that: The polyethylene glycol includes one or more of polyethylene glycol 4000, polyethylene glycol 6000, polyethylene glycol 8000, polyethylene glycol 10000 and polyethylene glycol 20000.
7. The environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to claim 6, characterized in that: The polyethylene glycol is a mixture of polyethylene glycol 4000 and polyethylene glycol 6000, and the mass ratio of polyethylene glycol 4000 to polyethylene glycol 6000 in the mixture is 2 to 5:1; or, the polyethylene glycol is a mixture of polyethylene glycol 8000 and polyethylene glycol 10000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 10000 in the mixture is 2 to 5:1; or, the polyethylene glycol is a mixture of polyethylene glycol 8000 and polyethylene glycol 20000, and the mass ratio of polyethylene glycol 8000 to polyethylene glycol 20000 in the mixture is 2 to 5:
1.
8. The method for preparing the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties according to any one of claims 1 to 7, characterized in that: The following steps are involved: Polyethylene glycol, water and citric acid-carbon dot complex are mixed in sequence to obtain the environmentally friendly water-based cutting fluid with excellent lubrication and anti-rust properties.
Citation Information
Patent Citations
Water-based cutting lubricating fluid with ultralow friction coefficient
CN113046163A
Super-lubricating water-based cutting fluid
CN113403131A
Cutting fluid for metal machining
CN107118839A
One-step method for preparing water-soluble lubricating fluid containing carbon dots
CN109233951A